Acid-sensing (proton-gated) ion channels (ASICs) (version 2019.4) in the IUPHAR/BPS Guide to Pharmacology Database. (2019) - Kellenberger, Stephan; Rash, Lachlan D.; Schild, Laurent
No abstract available